Anxiety, success hope and coping stress styles in highschool graduates - Gołuch, Dominik (Studia Psychologica: Theoria et praxis, 2011)
The aim of the study is to examine the difference in the change of anxiety level and of success hope in 6 months prior to leaving exam between groups with different styles of coping with stress. It is assumed that during this period the level of anxiety and hope will change depending on the preferred style of coping. In order to verify the hypotheses a group of 144 high school graduates was tested. The first survey took place 6 months and the other 14 days before final exams. The following tests were used: CISS, STAI, KNS. The results of this study indicate that the overall level of anxiety has increased in the research group and this increase was greatest in the emotions-focused group. However, the level of success hope significantly decreased in the group favoring task-oriented style. There were no significant changes observed in the level of success hope in the remaining groups.